Impact of self reflection training using Kawa model on quality of life and Academic performance among occupational therapy students - Punitha P; Sofia Williams (Journal of Associated Medical Sciences, 2026)
Background: Self-appraisal and reflection are crucial for occupational therapy students (OT) and practitioners, fostering learning and professional growth. The Kawa model, typically used clinically, may aid self-reflection by helping students recognize their strengths and challenges. However, while the model has been extensively studied in clinical settings, research on its application as a self-reflection tool for OT students remains limited. Objectives: This study aimed to evaluate the impact of self-reflection training using the Kawa model on the quality of life and academic performance of undergraduate occupational therapy students. Materials and methods: A randomized controlled trial was conducted. A total of 183 occupational therapy students were initially screened using the Study Skills Assessment Questionnaire. Based on poor and moderate study skill levels, along with teacher reports, 77 students met the inclusion criteria. Through simple randomization using the lottery method, 50 students were selected and assigned to either the experimental group (N=25) or the control group (N=25).The quality of life and academic performance were assessed using the WHOQOL-BREF and an academic performance scale. The experimental group received self-reflection training based on the Kawa model, while the control group underwent conventional occupational therapy for six months. Data analysis was performed using SPSS version 23.0, with paired and independent t-tests applied. Results: Post-test scores showed statistically significant improvements in the experimental group in both quality of life (p